2018
DOI: 10.1186/s12887-018-1274-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breastfeeding duration in a predominantly Māori population in New Zealand

Abstract: BackgroundAlthough breastfeeding duration in New Zealand’s indigenous Māori is shorter than in non-Māori, we know little about barriers or motivators of breastfeeding in this community. The aim of this analysis was to identify predictors for extended duration of breastfeeding amongst participants drawn from predominantly Māori communities in regional Hawke’s Bay.MethodsMother/baby dyads were recruited from two midwifery practices serving predominantly Māori women in mostly deprived areas, for a randomised cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
2
7
1
Order By: Relevance
“…Chinese women who strongly intended to breastfeed their babies were reported to practice EBF at a higher level (Wu, Ho, Han, & Chen, 2018). Similar results were reported for Maori women (Manhire et al, 2018). In the present study, the women who had a positive attitude toward breastfeeding and were supported by their husbands to breastfeed showed better breastfeeding self-management behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…Chinese women who strongly intended to breastfeed their babies were reported to practice EBF at a higher level (Wu, Ho, Han, & Chen, 2018). Similar results were reported for Maori women (Manhire et al, 2018). In the present study, the women who had a positive attitude toward breastfeeding and were supported by their husbands to breastfeed showed better breastfeeding self-management behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…This is in keeping with reports that most children are diagnosed later in life, possibly due to developmental trends, symptom overlap, and lack of physiological indicators, and this raises concern about the current ability to detect and consequently respond to the needs presented in young children with FASD (Rasmussen 2005 ; Rasmussen and Bisanz 2009 ; Temple et al 2019 ). On the other hand, the almost consistently lowest scores among the children with other NDDs likely result from the medical complexities common in that group (Williams et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study among working mothers in Hong Kong by Dodgson's [40] found that when infants are cared for by a nanny or older family member while the mother is working, the decision about breastfeeding duration is not in the mother's control. Previous studies have also found that family support [62] is significantly related to breastfeeding duration.…”
Section: Discussionmentioning
confidence: 78%